The (Mis-) Measurement of Fiscal Decentralization in Developing and Transition Countries: Accounting for Devolved and Nondevolved Local Public Sector Spending. (November 2016) - Boex, Jamie; Edwards, Benjamin
There is an extensive literature on the impact of fiscal decentralization on economic growth, development, and public sector effectiveness. However, the empirical literature on fiscal decentralization has exclusively focused on measuring the finances of elected or "devolved" local governments. Other types of decentralized expenditures, including deconcentrated and delegated expenditures, have been systematically excluded from measurement and analysis in the public finance and development literature. Our analysis considers the extent to which using devolved expenditures as a proxy for all devolved expenditures may have impacted the findings of the empirical literature. We collect comprehensive vertical expenditure profiles for health and education services in twenty-nine developing and transition countries and find that by exclusively focusing on devolution, previous analyses have overlooked two-thirds of local public sector expenditures. By excluding these "nondevolved" decentralized expenditures, the previous (often inconclusive) empirical analyses are likely to have suffered from omitted-variable bias.